An Analysis of Critical Thinking Ability of Elementary School Students Through Model Contextual Teaching and Learning on Social Learning - Syah, Imam Ma`arif; Suyahmo, Suyahmo; Utomo, Cahyo Budi (Journal of Primary Education)
Critical thinking ability of students in learning social science has not been measured in the learning process. The purpose of this study tests the effectiveness of the model Contextual Teaching and Learning (CTL) toward the students’ critical thinking ability, describe the process of analysis of students’ critical thinking ability. This type of study was a mixed-method, with sequential explanatory design. Samples of this study were grade V Public Elementary School 01 Rajekwesi, Jepara and Public Elementary School 01 Datar, Jepara. The data collection was conducted by a test, interview, and documentation. Quantitative data analysis techniques using the test and qualitative data analysis techniques with the triangulation of the data in the form of tests, interview, and documentation. The results showed that CTL model learning effectively improved critical thinking ability. Result of the average different test of the independent table column sig test sample (2-tailed) of 0.00 ˂ 0.05, this means that H1 accepted, the average critical thinking ability of CTL class is better than the expository class. Classical completeness of test results of the CTL class 80.95% students achieve at grade expository minimum completeness criteria (MCC), and that is equal to 76%. Test results of the average increase of the critical thinking ability in the classroom CTL by 30.33 and the expository class of 17.76. The description of the critical thinking ability of students in the expository class that belong to the criteria of good were the indicators of reasons and inference, which included in the criteria of moderate were an indicator of focus, situation, clarity, and overview. Meanwhile, in the classroom with CTL that belong to the good criteria were indicators of reasons, inference, focus, situation, clarity, whereas the overview included in the criteria of moderate.